Prevalence of hepatitis coinfection and substance use among antiretroviral therapy clinic clients with hazardous alcohol use in Vietnam. - Jane S Chen; Sara N Levintow; Ha V Tran; Adams L Sibley; Natalie A Blackburn; Teerada Sripaipan; Heidi E Hutton; Vivian F Go; Geetanjali Chander (PLOS Global Public Health)
The confluence of injection drug use (IDU), alcohol consumption, and viral hepatitis increases morbidity among persons living with HIV (PWH). We present a secondary analysis of a randomized controlled trial of alcohol reduction interventions in Thai Nguyen, Vietnam conducted between 2016-2018. We assessed hepatitis B (HBV) and hepatitis C (HCV) coinfection among PWH reporting hazardous alcohol consumption and examined differences in IDU and alcohol use by coinfection status. Participants were ≥18 years old, living with HIV, and reported hazardous alcohol consumption per the WHO Alcohol Use Disorders Identification Test Consumption (AUDIT-C; score ≥4 for men, score ≥3 for women). At enrollment, participants were tested for hepatitis coinfection with HBV surface antigen tests and rapid serological HCV tests. Demographic information, IDU, and recent alcohol consumption were assessed via behavioral survey and 30-day timeline follow back. Fishers Exact and Kruskal-Wallis tests were used for statistical testing. Hepatitis coinfection was common among the 440 enrolled PWH: HCV: n = 355 (81%); HBV: n = 5 (1%); HBV and HCV: n = 37 (8%). Only 10% (n = 43) of participants had no hepatitis coinfection. Among those who tested positive for HBV, 36% had previously been diagnosed with HBV; among those who tested seropositive for HCV, 18% had previously received an HCV diagnosis. History of IDU was higher among those with hepatitis coinfection (HBV or HCV coinfection: 88%; HBV and HCV coinfections: 97%) than those without hepatitis coinfection (7%; p<0.01). Median days of alcohol consumption in the last 30 days was higher among those with coinfection (HBV or HCV coinfection: 20 (Interquartile Range (IQR): 10-30); HBV and HCV coinfections: 22 (IQR: 13-28) than those without hepatitis coinfection (10; IQR: 6-21; p<0.01). The syndemic conditions of HIV, hepatitis, IDU, and alcohol use are deeply entangled and challenging to parse out. Integrated health services are warranted to reduce the risk of liver-related morbidity.